Cyclophilin D-mediated regulation of the permeability transition pore is altered in mice lacking the mitochondrial calcium uniporter. Issue 2 (27th August 2018) - Parks, Randi J; Menazza, Sara; Holmström, Kira M; Amanakis, Georgios; Fergusson, Maria; Ma, Hanley; Aponte, Angel M; Bernardi, Paolo; Finkel, Toren; Murphy, Elizabeth
Abstract: Aims: Knockout (KO) of the mitochondrial Ca 2+ uniporter (MCU) in mice abrogates mitochondrial Ca 2+ uptake and permeability transition pore (PTP) opening. However, hearts from global MCU-KO mice are not protected from ischaemic injury. We aimed to investigate whether adaptive alterations occur in cell death signalling pathways in the hearts of global MCU-KO mice. Methods and results: First, we examined whether cell death may occur via an upregulation in necroptosis in MCU-KO mice. However, our results show that neither RIP1 inhibition nor RIP3 knockout afford protection against ischaemia-reperfusion injury in MCU-KO as in wildtype (WT) hearts, indicating that the lack of protection cannot be explained by upregulation of necroptosis. Instead, we have identified alterations in cyclophilin D (CypD) signalling in MCU-KO hearts. In the presence of a calcium ionophore, MCU-KO mitochondria take up calcium and do undergo PTP opening. Furthermore, PTP opening in MCU-KO mitochondria has a lower calcium retention capacity (CRC), suggesting that the calcium sensitivity of PTP is higher. Phosphoproteomics identified an increase in phosphorylation of CypD-S42 in MCU-KO. We investigated the interaction of CypD with the putative PTP component ATP synthase and identified an approximately 50% increase in this interaction in MCU-KO cardiac mitochondria. Mutation of the novel CypD phosphorylation site S42 to a phosphomimic reduced CRC, increased CypD-ATP synthase interaction by approximately 50%, and increased cell death in comparison to a phospho-resistant mutant. Conclusion: Taken together these data suggest that MCU-KO mitochondria exhibit an increase in phosphorylation of CypD-S42 which decreases PTP calcium sensitivity thus allowing activation of PTP in the absence of an MCU-mediated increase in matrix calcium.